DigDesFab15 Research Pavilion - Gheorghe, Andrei; Vierlinger, Robert (Frontiers in Digital Humanities, 2017)
This full-scale research pavilion exercises the application of timber and polymer concrete in architectural production (Fig. 1). It attempts to develop and test a new hybrid construction technique using composite joints (as introduced in Schober, 2014) within a modular geometric system and no need for formwork. The structure was designed and erected by students and instructors of the Digital Design and Full Scale Fabrication seminar taught at the University of Applied Arts Vienna. CNC milled, 3-layer spruce laminated timber boards are used for construction, which are temporarily fixed, then rigidized with polymer concrete. The cured composite node proves high structural capabilities, as polymer concrete withstands both pressure and tensile forces, and the bond between the materials is as strong as the wood itself. Compared to traditional timber construction, no metal bolting is needed for the creation of the node, while at the same time the node geometry becomes more flexible, meaning any three-dimensional layout can be produced, as long as a temporary containment and fixation can be implemented until the chemical curing process is completed (Becker, Schober, Weber, 2016). The geometry is developed as an interpretation of the Zollinger (Menges A. et al., 2016) grid, where members originally are of twice the grid length (Fig. 2) and reciprocally reliant on each other (Fig. 3). Instead, every second grid cell is made a joint node when cast out with concrete, making the structural members a lost formwork at the same time (Fig. 4). Double-layering each makes it possible to cast all 122 nodes of the pavilion structure separately and flat-bolt them together on-site with metal screws. The software plugin RhinoVault is used as a design tool to produce an efficient, compression only basic shell surface, although the subsequent imposition of the grid system introduces eccentricities and local imperfections. A parametric model in Rhinoceros and Grasshopper tests various subdivision densities and node sizes, and evaluates the overall performance with the structural analysis tool Karamba. The different heights of the lamellas in the structure arise from the analysis and parametric interpretation of stresses under vertical and horizontal loading.